ANALISIS STRATEGIS SEKOLAH DASAR NEGERI KOTA TASIKMALAYA DI ERA DISRUPTIF DALAM MENINGKATKAN MUTU PENDIDIKAN - Indi Widiyanti; Santi Susanti; Ichsan Fauzi Rachman (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Schools as educational institutions have an important and crucial role in creating a high-quality generation for the nation. Efforts to increase the potential and quality of education certainly require significant support from both the community and the government. But improving the quality of education is not easy. There are definitely several problems that can hinder the process of improving the quality of education. Therefore, effective strategies are needed to improve the quality of education. The research method used is using a literature review or literature study. The data collection technique is by reading and analyzing data sourced from the internet, scientific journals, e-books and official websites. This technique is used to obtain a basis and written opinion by studying various literature regarding the problem being studied. Keywords: Disruptive Era, Quality of Education, Elementary School.